Evaluación del desempeño del mineral barita de la Sierra Nevada de Santa Marta como densificante para la implementación en un fluido de perforación base agua a nivel de laboratorio (2020)
The following is the grade work that has as its purpose the characterization of the barite ore collected from the Sierra Nevada de Santa Marta and Altos de la Guajira, such as the study of the behavior and performance of barite in water based drilling muds, all this taken to laboratory scale, to finish with the cost benefit of the implementation of the collected barite. Three types of barite were taken into account, which for methodological purposes are mentioned as the conventional one (used in the mud and water laboratories at the University of America Foundation), the one from the Sierra Nevada de Santa Marta and the one from Altos de la Guajira. It is concluded that the barite studied in both the Sierra Nevada de Santa Marta and Altos de la Guajira has physical-chemical properties suitable for use in water-based drilling muds, has much lower costs compared to imported products, and although its low density would not allow it to compete in international markets, its cost would advantageously compensate for the higher material to be dosed for type mixtures such as those studied here.